Innovative approaches to application of information technology in disease surveillance and prevention in western Kenya - Odero, W.; Rotich, J.; Yiannoutsos, C.T.; Ouna, T.; Tierney, W.M. (Elsevier, 2007)
We describe an electronic injury surveillance system that provides data for improving patient care and monitoring injury incidence and distribution patterns. Patients with injuries visiting a rural Kenyan primary care center were enrolled consecutively over 14 months. Injury information was added onto an existing medical record database that captures data for each patient visit. A new injury data encounter form and entry screen were created that included geographical coordinates of the injury site. These coordinates were obtained using a handheld global positioning system (GPS) device, and data were downloaded to the database and linked to each patient. We created digital maps of injury spatial distribution using geography information systems (GIS) software and correlated injury type and location with patients'clinical data. A computerized medical record system, complemented by GIS technology and an injury-specific component, presents a valuable tool for injury surveillance, epidemiology, prevention and control for communities served by a specific health facility.